Further Investigation Into the Mechanism of Tachykinin NK2 Receptor- Triggered Serotonin Release From Guinea-Pig Proximal Colon - Shu-ichi Kojima; Masashi Ikeda; Yuichiro Kamikawa (Elsevier, 2009)
Abstract.: The effects of the monoamine oxidase A (MAO-A) inhibitor clorgyline, the L-type calcium-channel blocker nicardipine, the syntaxin inhibitor botulinum toxin type C, and the potent thiol-oxidant phenylarsine oxide (PAO) on the selective tachykinin NK2-receptor agonist [β-Ala8]-neurokinin A4-10 [βAla-NKA-(4-10)]-evoked 5-hydroxytryptamine (5-HT) outflow from colonic enterochromaffin (EC) cells was investigated in vitro using isolated guinea-pig proximal colon. The βAla-NKA-(4-10)-evoked outflow of 5-HT from clorgyline-treated colonic strips was markedly higher than that from clorgyline-untreated colonic strips. The βAla-NKA-(4-10)- evoked 5-HT outflow from the clorgyline-treated colonic strips was sensitive to nicardipine or botulinum toxin type C. Moreover, PAO concentration-dependently suppressed the βAla-NKA-(4-10)-evoked 5-HT outflow from the clorgyline-treated colonic strips. The suppressant action of PAO was reversed by the reducing agent dithiothrietol, but was not blocked by the protein tyrosine kinase inhibitor genistein. These results suggest that the tachykinin NK2 receptor- triggered 5-HT release from guinea-pig colonic EC cells is mediated by syntaxin-related exocytosis mechanisms and that colonic mucosa MAO-A activity has the important function of modulating the tachykinin NK2 receptor-triggered 5-HT release. It also appears that PAO-mediated sulfhydryl oxidation plays a role in modulating the tachykinin NK2 receptor-triggered 5-HT release through a mechanism independent of inhibition of protein tyrosine phosphatase activity. Keywords:: colon, serotonin, tachykinin